Phổ hồng ngoại, cấu trúc và tính chất nhiệt của vật liệu polyme blend trên cơ sở polyaxit lactic và copolyme etylen-vinylaxetat - Hoang, Thai; Công, Đỗ Văn; Sumita, Masao (Vietnam Journal of Chemistry, 2014)
Polylactic acid is one of the most popular bioplastics used in recent years and it is often mixed with other polymers or chemicals to form polymer blend because polylactic acid is able to accelerate biodegradation of polymer blends. This paper presents some results of study on polymer blend based on polylactic acid (PLA) and ethylene-co-vinylacetate copolymer (EVA). Fourier transform infrared spectroscopy of polymer blend PLA/EVA shows that position of peaks of C=O, C-O-C groups shifts to intermediate position characterized these groups in PLA and EVA due to their dipole-dipole interactions. These interactions make PLA and EVA disperse into each other more regularly. The presence of PLA increases slightly initial degradation temperature of polymer blend with PLA contents of 20 - 60 wt.%. EVA enhances oxidation thermostability of polymer blend at high temperatures.